2010
DOI: 10.4314/njps.v23i1-2.54931
|View full text |Cite
|
Sign up to set email alerts
|

Methanolic extract of tetracera potatoria, an antiulcer agent increases gastric mucus secretion and endogenous antioxidants

Abstract: Summary: In this study, the possible mechanism underlying the antiulcer activity of the methanolic extract of the root of Tetracera potatoria (MeTp) was studied in albino rats. Misoprostol and omeprazole were used as reference drugs. The animals had MeTp administered to them at varying doses of 100, 400 and 800 mg/kg for 15 days. MeTp significantly (P<0.05) increased gastric mucus secretion and gastric mucus cell counts when compared to control. MeTp treated animals also showed significant (P<0.05) increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…The pathogenesis of ethanol-induced gastric mucosal damage occurs directly and indirectly through various mediators such lipoxygenase, cytokines, and oxygen-derived free radicals [32]. Mucus secretion is regarded as a crucial defensive factor in the protection of the gastric mucosa from gastric lesions [33]. …”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of ethanol-induced gastric mucosal damage occurs directly and indirectly through various mediators such lipoxygenase, cytokines, and oxygen-derived free radicals [32]. Mucus secretion is regarded as a crucial defensive factor in the protection of the gastric mucosa from gastric lesions [33]. …”
Section: Discussionmentioning
confidence: 99%
“…H 2 blockers like cimetidine, ranitidine, and famotidine exhibit antihistaminic effect thus causing reduction in gastric acidity and secretory volume since they have a five-membered ring structure with a flexible side chain attached to polar uncharged group. Evidently, betulinic acid an active constituent in both the extracts having similar ring structure to H 2 blockers may be a reason for the antihistaminic effect, which is responsible for gastroprotective nature [39, 40]. Moreover, betulinic acid, lupeol, betulin, and glycosides [31, 41–44] present in the extracts possess potent antioxidant properties by decreasing lipid peroxidation and increasing antioxidant levels.…”
Section: Discussionmentioning
confidence: 99%
“…In fact major, the compounds are known by their antiulcer effects by inhibition of the lesions of the gastric mucous membrane [18]. It was also reported that the flavonoïds ensures a protection against gastric cancer [19,20].…”
Section: Discussionmentioning
confidence: 99%